2015
DOI: 10.1037/pas0000100
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Short Form of the Five-Factor Narcissism Inventory: The FFNI-SF.

Abstract: The Five-Factor Narcissism Inventory (FFNI; Glover, Miller, Lynam, Crego, & Widiger, 2012) is a 148-item self-report inventory of 15 traits designed to assess the basic elements of narcissism from the perspective of a 5-factor model. The FFNI assesses both vulnerable (i.e., cynicism/distrust, need for admiration, reactive anger, and shame) and grandiose (i.e., acclaim seeking, arrogance, authoritativeness, entitlement, exhibitionism, exploitativeness, grandiose fantasies, indifference, lack of empathy, manipul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
161
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 180 publications
(183 citation statements)
references
References 25 publications
(36 reference statements)
12
161
0
10
Order By: Relevance
“…No significant relationships between the FFNI-SF and BigFive Personality Trait scores were obtained from the TIPI. In the original study (Sherman et al, 2015), low yet significant relationships were found in the undergraduate sample, and moderate-to-high correlations were found in the clinical sample.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…No significant relationships between the FFNI-SF and BigFive Personality Trait scores were obtained from the TIPI. In the original study (Sherman et al, 2015), low yet significant relationships were found in the undergraduate sample, and moderate-to-high correlations were found in the clinical sample.…”
Section: Discussionmentioning
confidence: 99%
“…RMSEA values should be between .050 and .080 for acceptable levels of fit, and below .050 for perfect levels of fit to the data (Brown & Cudeck, 1993;Byrne & Campbell, 1999 The models were derived from the original study of Sherman et al (2015). According to the CFA results, the model with 60 items and 15 factor-loadings fit the data best (Model 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations